PENGEMBANGAN KAPASITAS KELOMPOK USAHA PERHUTANAN SOSIAL (KUPS) AEK BIGHA DI HUTAN ADAT GHIMBE PERAMUNAN DESA PENYANDINGAN KECAMATAN SEMENDO DARAT LAUT KABUPATEN MUARA ENIM OLEH HUTAN KITA INSTITUTE - Henni Martini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The capacity building program for the KUPS Aek Bigha in the Ghimbe Peramunan Customary Forest, which is administratively located within the village of Penyandingan, is driven by the abundant potential of robusta coffee. The main challenges faced are the long supply chain and price fluctuations, while the community only sells coffee in the form of green beans. Through mentoring and training provided by the Hutan Kita Institute (HaKI), this program focuses on product downstreaming. The activities carried out include needs identification, coffee processing training using roasting machines, institutional management, and digital marketing. The goals are to increase the added value of coffee, the institutional capacity of the group, and to encourage the improvement of household economies and the sustainability of customary forest management.